1987
DOI: 10.1104/pp.84.4.1331
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis in Bromegrass (Bromus inermis Leyss) Cultured Cells during the Induction of Frost Tolerance by Abscisic Acid or Low Temperature

Abstract: Bromus inermis Leyss cell cultures treated with 75 micromolar abscisic acid (ABA) at both 23 and 3°C developed more freezing resistance than cells cultured at 3°C. Protein synthesis in cells induced to become freezing tolerant by ABA and low temperature was monitored by I'4Cileucine incorporation. Protein synthesis continued at 3°C, but net cell growth was stopped. Most of the major proteins detected at 23°C were synthesized at 3WC. However, some proteins were synthesized only at low temperatures, whereas othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 23 publications
3
43
0
Order By: Relevance
“…The first pattern (A) includes transcripts that were detected primarily after ABA treatment. This type of response is similar to that of the cold-responsive genes identified in other species (Robertson et al, 1987;Mohapatra et al, 1988Mohapatra et al, , 1989Cattivelli and Bartels, 1990;Hajela et al, 1990;Kurkela and Franck, 1990;Lu0 et al, 1992). With the second pattem (B) of gene expression, transcripts were detected in the controls but were up-regulated by ABA or cold treatment.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The first pattern (A) includes transcripts that were detected primarily after ABA treatment. This type of response is similar to that of the cold-responsive genes identified in other species (Robertson et al, 1987;Mohapatra et al, 1988Mohapatra et al, , 1989Cattivelli and Bartels, 1990;Hajela et al, 1990;Kurkela and Franck, 1990;Lu0 et al, 1992). With the second pattem (B) of gene expression, transcripts were detected in the controls but were up-regulated by ABA or cold treatment.…”
Section: Discussionsupporting
confidence: 83%
“…With bromegrass (Bromus inermis) cell cultures, it has been demonstrated that 4 to 5 d of ABA treatment increases freezing tolerance by 23OC, with a change in from -7 to -3OOC (Chen and Gusta, 1983;Lee et al, 1991). Associated with a rapid increase in hardiness were qualitative changes in the population of polypeptides (Robertson et al, 1987) and translatable RNAs (Lee et al, 1991). Deacclimation of ABA-hardened bromegrass cells is a relatively slow process (Reaney et al, 1989;Lee et al, 1991) compared to other coldhardy species (Guy et al, 1985;Hajela et al, 1990;Tseng and Li, 1990).…”
mentioning
confidence: 99%
“…ABA is known to accumulate during cold acclimation of plants . Also, there have been many studies that suggest that ABA may be a mediator of cold tolerance in plants (Robertson et al, 1987;Thomashow, 1990). In addition, exogenous application of ABA has been shown to increase cold tolerance in whole plants and cell cultures, to substitute the cold-acclimation treatment, and to cause the expression of proteins associated with cold acclimation (Chen and Gusta, 1983;Robertson et al, 1987).…”
Section: Aba and Negative Pressuresmentioning
confidence: 99%
“…However, it is not known how these cell-wall changes affect the physical properties of cell walls in relation to their ability to undergo deformation during freezing. Also, cold acclimation is known to be associated with the accumulation of ABA, which is believed to be responsible for induction of changes associated with cold acclimation in plants Reaney and Gusta, 1987;Robertson et al, 1987).…”
mentioning
confidence: 99%
“…Upon exposure to low temperature, both activities of the tonoplast H+-ATPase, substrate hydrolysis and proton transport declined rapidly, reaching a minimum within 10 h. This effect appears far earlier than irreversible cell injury. On the contrary, no cold-induced inactivation was observed in the tonoplast H+-ATPase in suspension cultured cells of bromegrass (Table I), which are reported to be capable of cold hardening (12,13). Therefore, there seems to be a marked difference in the cold stability of tonoplast H+-ATPase in vivo between chilling-sensitive and -resistant cultured cells.…”
Section: Discussionmentioning
confidence: 87%